2018
DOI: 10.1111/cod.13056
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of skin and surfaces by cobalt in the hard metal industry

Abstract: Cobalt skin doses were prominent, and originated from contact with raw materials, sintered materials, and contaminated surfaces. Cobalt was present on surfaces outside production areas. Companies need to identify and reduce skin exposure for protection of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…There are still no requirements to test Co release from items intended to come in prolonged and/or frequent skin contact such as with Ni. In our study the highest amount of Co was on the fingers of the nail heaters and raw material operators in concordance with other studies in which the highest quantity was found on hard metal pressing operator 19 and raw material groups 20,21 . These occupations have the most contact with raw unprocessed goods.…”
Section: Discussionsupporting
confidence: 92%
“…There are still no requirements to test Co release from items intended to come in prolonged and/or frequent skin contact such as with Ni. In our study the highest amount of Co was on the fingers of the nail heaters and raw material operators in concordance with other studies in which the highest quantity was found on hard metal pressing operator 19 and raw material groups 20,21 . These occupations have the most contact with raw unprocessed goods.…”
Section: Discussionsupporting
confidence: 92%
“… 6 10 14 15 Sources of Co skin exposure within the hard metal industry have recently been identified and included the deposition of particles and dust, handling of hard metal items during production as well as touching production equipment and other work materials. 16 …”
Section: Introductionmentioning
confidence: 99%
“…But more often incorrect use of protective gloves occurs, and the wrong type of gloves is used so that the skin is not protected. A recently published study show that workers’ glove use did not affect the amount on cobalt deposited on skin in a hard metal facility due to the factors mentioned above ( Kettelarij et al , 2018b ). Furthermore, the efficiency of washing off metals from the skin has been investigated in some studies, showing that cobalt, chromium, iron, nickel, and lead, remain on the skin surface even after thorough cleaning ( Linnainmaa and Kiilunen, 1997 ; Sato and Yano, 2006 ; Liden et al , 2008 ; Lewinski et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%